The Effectiveness of CBT with a Self-Talk Technique in Reducing Communication Anxiety - Sarri, Mei; Mugiarso, Heru; Sugiyo, Sugiyo (Study Program of Guidance and Counselling, Post Graduate Program, Universitas Negeri Semarang, 2024)
Intense communication anxiety can potentially disrupt social interactions and hinder students' ability to communicate effectively. Regarding this issue, the present research examined the effectiveness of a Cognitive Behavioral Therapy (CBT) approach with a self-talk technique to resolve communication anxiety in students. Using a pretest-posttest control group design, this research included 14 students divided into an experimental group and a control group. Data of their behavior was collected using a communication anxiety scale that previously has been tested for validity and reliability. Following the collection, an intervention was carried out in five sessions to determine whether the self-talk technique applied through CBT was able to significantly affect student’ anxiety. Surely, the findings of this research provide practical contributions to the application of CBT techniques in counseling and education, as well as broaden the understanding of psychological interventions for communication anxiety problems. Future research should involve larger sample sizes and longer intervention durations. Counselors are recommended to use CBT with self-talk techniques, provide ongoing support, and offer feedback and strategy adjustments based on students' needs.